Digital Services of Public Government Administration In The Industrial Revolution 4.0 - Kurniawan, Mulyono; Khalimi, Khalimi (SASI, 2023)
Introduction: Technology and the Industrial Revolution 4.0 have enabled the development of e-government for faster and more effective services. However, its implementation still needs to be improved, particularly regarding legal certainty.. Purposes of the Research: This study aims to analyze the legal uncertainty that occurred in the implementation of e-government in the Industrial Revolution 4.0 era. Methods of the Research: This research is normative legal research with a statutory and conceptual approach. The primary legal materials in this research include the 1945 Constitution of the Republic of Indonesia and the laws governing State Government administration. Secondary legal materials include books, articles, and research results. Non-legal material includes all non-legal studies related to electronic-based State Government Administration systems / e-government.Results of the Research: The study results provide an analysis of the constraints that occur in the implementation of Digital Government Administration. There needs to be an evaluation of the government's readiness in the e-government system, the affordability of the internet, the availability of server capacity that can accommodate many data, and the electronic devices used do not meet standards. It is suggested that the government must provide all technical and non-technical aspects that can support e-government performance as well as provide human resources who are experts in their fields, so that the government administration service system complies with the General Principles of Good Government (AUPB). It can be realized promptly by the principle of legal certaint.